Persistent feeding difficulties among infants with fetal opioid exposure: mechanisms and clinical reasoning. (2nd November 2019) - Hart, Brandon J.; Viswanathan, Sreekanth; Jadcherla, Sudarshan R.
Abstract: Aims: Infants with fetal exposure to opioids have varying pattern of feeding difficulties mainly manifesting as difficulties with aerodigestive adaptation and disruptive feeding behavior. The reasons are unclear; in a pilot study, we determined basal and adaptive pharyngo-esophageal motility in a group of infants with fetal exposure to opioids and persistent feeding difficulties impeding their discharge. Methods: Six infants with fetal opioid exposure compared to 12 controls who underwent basal and adaptive pharyngo-esophageal manometry to characterize the basis for their symptoms. Spontaneous swallows ( N = 180) and pharyngeal stimuli ( N = 113)-induced swallowing responses were analyzed. Results: Resting upper esophageal sphincter (UES) pressure was similar in both the groups, but resting lower esophageal sphincter (LES) pressure was significantly high and it relaxed slowly and inadequately in opioid-exposed infants ( p < .05). Upon pharyngeal provocation, opioid-exposed infants had higher LES nadir pressure, increased duration of esophageal body contraction at proximal-, mid-, and distal-esophagus, as well as greater area under the curve with distal esophageal waveforms, compared to controls (all p < .05). Conclusions: These pilot observations are suggestive of up-regulation of central vagal effects with heightened cholinergic excitatory responses and inadequate relaxation responses at the foregut, and may form the basis for persistent feeding difficulties in opioid-exposed infants. Abnormality with both sensory and motor aspects of vagal reflexes may be contributory.